Secreted Peptide PIP1 Induces Stomatal Closure by Activation of Guard Cell Anion Channels in Arabidopsis - Shen, Jianlin; Diao, Wenzhu; Zhang, Linfang; Acharya, Biswa R.; Wang, Mei; Zhao, Xiangyu; Chen, Donghua; Zhang, Wei (Frontiers in Plant Science, 2020)
ABSTRACT Plant stomata which consist of a pair of guard cells, are not only finely controlled to balance water loss as transpiration and CO2 absorption for photosynthesis, but also serve as the major sites to defend against pathogen attack, thus allowing plants to respond appropriately to abiotic and biotic stress conditions. The regulatory signaling network for stomatal movement is complex in nature, and plant peptides have been shown to be involved in signaling processes. Arabidopsis secreted peptide PIP1 was previously identified as an endogenous elicitor, which induced immune response through its receptor, RLK7. PIP1-RLK7 can activate stomatal immunity against the bacterial strain Pst DC3118. However, the molecular mechanism of PIP1 in stomatal regulation is still unclear and additional new factors need to be discovered. In this study, we further clarified that PIP1 could function as an important regulator in the induction of stomatal closure. The results showed that PIP1 could promote stomata to close in a certain range of concentrations and response time. In addition, we uncovered that PIP1-RLK7 signaling regulated stomatal response by activating S-type anion channel SLAC1. PIP1-induced stomatal closure was impaired in bak1, mpk3 and mpk6 mutants, indicating that BAK1 and MPK3/MPK6 were required for PIP1-regulated stomatal movement. Our research further deciphered that OST1 which acts as an essential ABA-signaling component, also played a role in PIP1-induced stomatal closure. In addition, ROS participated in PIP1-induced stomatal closure and PIP1 could activate Ca2+ permeable channels. In conclusion, we reveal the role of peptide PIP1 in triggering stomatal closure and the possible mechanism of PIP1 in the regulation of stomatal apertures. Our findings improve the understanding of the role of PIP1 in stomatal regulation and immune response. Keywords: guard cells, secreted peptide, PIP1, stomatal closure, anion channel